MORAL CONFLICT AND AESTHETIC FREEDOM: A STUDY OF CONTEMPORARY MUSIC PHILOSOPHY FROM THE PERSPECTIVE OF IMMANUEL KANT AND FRIEDRICH NIETZSCHE - Saragih, Kantri Sajojo (Institut Seni Indonesia (ISI) Surakarta, 2025)
The evolution of contemporary music has created a tension between universal moral demands and artistic expressive freedom. This study analyzes this dialectic through the philosophical lenses of Immanuel Kant and Friedrich Nietzsche. Kant emphasizes aesthetics as a universal experience bound by morality, while Nietzsche liberates art from traditional conventions in favor of transgressive creative expression. The research examines radical works such as 4'33